VRB high-strength steel-CFRP B-pillar assembly material-structure-process synergistic lightweight design and multilevel optimization approach - Zhang, Shuai; Ma, Yun-Long; Guo, Jia-hao; Zhang, Jin-yuan; Xi, Zhi-qiang; Wang, Yi-liu; Xiong, Feng; Yan, Mi; Zhang, Hao; Deng, Heng (Journal of materials research and technology, 2025)
To enhance the safety performance and lightweight design level of the B-pillar assembly, this article proposes the collaborative design concept and processing method of variable-thickness high-strength steel-carbon fiber composite B-pillar assembly design, optimization and process molding. Established the finite element analysis models of the B-pillar and the body-in-white, and conducted verification. Determined the structural scheme of the B-pillar reinforcement plate, through the experimental tests of the basic performance parameters of the T700/WP-R2300 composite, and the lay-up design and multi-level optimization of the Carbon Fiber Reinforced Plastic (CFRP) B-pillar reinforcement plate. Designed the composition of low-cost micro-alloyed high-strength steel and the forming process parameters, and conducted mechanical property verification. Combined with the previously proposed improved PSO–BFO (Particle Swarm optimization algorithm - bacterial foraging algorithm) hybrid optimization algorithm and its multi-objective optimization method, the multi-objective optimization of the outer plate of the Variable thickness Rolled Blanks (VRB) high-strength steel B-pillar was carried out under multiple working conditions to obtain the Pareto solution set. The simulation comparison of the B-pillar assembly performance before and after optimization shows that the weight of the B-pillar assembly is reduced by 13.52 %, while the tensile stiffness, side-bending stiffness, rear-bending stiffness and three-point bending stiffness are increased by 18.93 %, 6.40 %, 9.66 % and 49.66 % respectively. Additionally, the first-order bending-torsion mode is increased by 46.82 % and 11.90 % respectively. These results validate the effectiveness of the proposed design scheme and the multi-level multi-objective optimization methodology. The B-pillar reinforcement plate was manufactured by using the improved vacuum-assisted resin transfer molding (VARTM) process, while the B-pillar VRB high-strength steel outer plate was manufactured through a combined hot stamping and carbon partitioning process. The outer plate and reinforcement plate were connected by adhesive bonding technology, followed by comparative modal testing and experimental verification. The discrepancy between simulation and experimental results was maintained within 6 %. The displacements under the bending and torsional conditions of the body-in-white were reduced by 24.80 % and 1.97 %, respectively, significantly enhancing the stiffness of both the body-in-white and the B-pillar assembly. These results confirm the validity and effectiveness of the proposed methodology and technical solution.